Integrative analysis of transcriptome and metabolome reveals molecular mechanisms of dynamic change of storage substances during dehydration and drying process in peanuts (Arachis hypogaea L.) - Deng, Jingjing; Hou, Mingyu; Cui, Shunli; Liu, Yingru; Li, Xiukun; Liu, Lifeng (Frontiers in Plant Science, 2025)
Various substances in seeds occurred many transformations during the drying process, which is key to long-term storage, but the mechanism is unclear. In this study, seeds of the peanut (Arachis hypogaea L.) variety “Silihong” were selected as the experimental materials. Transcriptome and metabolome analyses of the peanut kernels at day 0 (S0d), day 1 (S1d), day 3 (S3d), day 5 (S5d), and day 7 (S7d) of drying were performed to search for the genes that controlled the storage compounds. A total of 165 differentially expressed metabolites (DAMs) and 15,010 differentially expressed genes (DEGs) in the five stages of seed drying were identified. S3d was the key period during which the content of most of the metabolites changed significantly. The contents of most amino acids(87%) and their derivatives decreased significantly, and most of the lipids(68%), sugars(67%) and flavonoids(87%) accumulated to their peak at S3d. A Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis revealed that the DEGs were primarily enriched in four aspects, including amino acid biosynthesis and metabolism, lipid biosynthesis and metabolism, sucrose and starch metabolism, and flavonoid biosynthesis. Crucial genes that potentially regulate the storage substances were identified, including PAL, FAD2, SUS, LOX, and PFK. Overall, this study provides valuable insights into the molecular regulation of storage compounds in peanut seeds and may help to assess edible peanuts that have enhanced nutritional and economic values.